BALANCING SCHOOL DURATION AND HEALTH: IMPACTS ON STUDENTS' WELL-BEING AND POLICY INSIGHTS - Talib, Burhanuddin (Universitas PGRI Palembang, 2025)
The length of school hours has a significant impact on students' physical and mental health, raising concerns about balancing academic demands with well-being. In countries like Indonesia, long school hours often lead to issues like fatigue, stress, and poor nutrition. Conversely, countries with shorter school days, such as Finland, show better health outcomes. This study aims to explore the relationship between school hours and student health, providing evidence-based recommendations for education policy reform. Its innovative approach compares different cultural and educational contexts, including Indonesia, to highlight region-specific effects. Using qualitative methods, the research involved interviews, observations, and document analysis, gathering data from students, parents, and teachers. Findings suggest that longer school hours negatively affect physical activity, sleep, and overall well-being, while shorter hours and later start times improve mental health and academic engagement. Indonesia’s Karja Sezi program demonstrates the effectiveness of policies, like regulated meals, in reducing health risks. This study contributes to discussions on education and health, offering actionable insights for policymakers to create balanced school schedules that support both academic success and student well-being.